Does women's place of birth affect their opportunity for an informed choice about Down syndrome screening? A population-based study in France - Olivia Anselem; Marie-Josèphe; Babak Khoshnood; Béatrice Blondel; Priscille Sauvegrain; Nathalie Bertille; Elie Azria; for the BiP study group (BMC, 2021)
Abstract Background To examine disparities by maternal place of birth in the opportunity to make an informed choice about Down syndrome screening, in France, where the national guidelines recommend that physicians offer it to all pregnant women. Methods We used population-based data from the nationally representative French Perinatal Surveys in 2010 and 2016 (N=24,644 women) to analyze the opportunity for an informed choice for prenatal screening, measured by a composite indicator. Results Among the 24 644 women in the study, 20 612 (83.6%) were born in France, 861 (3.5%) elsewhere in Europe, 1550 (6.3%) in North Africa, and 960 (3.9%) in sub-Saharan Africa. The probability of screening was lower for women born outside France. After adjustment for survey year, maternal age, parity, education level, and the maternity unit's level of perinatal care, women born outside France had the opportunity to make an informed choice less often than women born in France. This association remained essentially the same even after excluding women without adequate prenatal care. Conclusions Women born outside France, including those with adequate prenatal care, had less opportunity than women born in France to make an informed choice about prenatal screening for Down syndrome.